Comparative In Vitro antimicrobial activity of selected four medicinal plant leaves - Gowri, R.; Panambara, P.A.H.R.; Vinotha, S. (University of Jaffna, 2022)
In the treatment of diabetes mellitus, the traditional medical system of Sri Lanka has demonstrated to be far more effective, with less side effects and lower costs than modern synthetic medications. Ethnobotanical research is also necessary to learn about the world's traditional usage for treating chronic illness. Therefore, the present evaluation was aimed to compare the antimicrobial activity between the ethanolic leaves extracts of Murraya koenigii, Tinospora cordifolia, Enicostemma littorale and Gymnema sylvestre which are commonly found in Jaffna District against three different bacterial species such as Staphylococcus sp., Enterococcus sp. and Escherichia coli sp. by determining zone of inhibition using agar well diffusion method and compared with standard antibiotics. All experiments were conducted in triplicate. The statistical analysis was carried out using one-way Analysis of variance and values were expressed as the mean ± standard deviation. Results showed all the tested leaf extracts showed promising antibacterial activity against all the bacterial strains which was comparable with positive control Streptomycin. E.littorale showed the highest zone of inhibition diameter against Enterococcus sp. (14.08±2.46 mm). M.koenigii showed the highest zone of inhibition diameter against Staphylococcus sp. (8.96±2.49 mm) and E.coli (9.67±0.996 mm). Present study determined that the ethanol leaf extracts of Murraya sp. and Enicostemma sp. showed the highest antibacterial activity than other two species against all tested bacteria. Therefore, E.littorale and Enicostemma sp. can be used for developing therapeutic agents for the treatment of infectious diseases caused by microbes in future.
Keywords: Agar well diffusion; Antibacterial activity; Inhibition zone; Medicinal plant leaves